A Rare Cause of Infectious Tenosynovitis: Cardiobacterium hominis Endocarditis - Simon Stutz; Roberto Buonomano; Alain Rudiger; Elias Bodendoerfer; Thomas Herren (Annals of Internal Medicine: Clinical Cases)
Infectious tenosynovitis as a presenting symptom of infective endocarditis (IE) is unusual. We report the case of a 65-year-old man admitted for surgical aortic valve replacement 6 years previously who presented with ankle pain. Targeted imaging revealed septic emboli in the tibialis posterior tendon, kidney, and the brain. Cardiobacterium hominis was identified in blood cultures, and the diagnosis of IE was confirmed by echocardiography. Portal of entry was a fractured and infected tooth, which was removed. Antibiotic treatment with ceftriaxone was successful. Atraumatic infectious tenosynovitis caused by hematogenous spread should raise the suspicion of IE.